Prerequisites and Perceived Information System Qualities Model for Mobile Banking Adoption Among the Customers of Private Commercial Banks in Myanmar - Phyo Min Tun (JAS (Journal of ASEAN Studies), 2021)
The research attempts to conjecture the prerequisites of perceived qualities of information system (IS) such as mobile banking (MB). The quantitative research was conducted and a total of 577 MB users of private commercial banks in Myanmar participated in the research. The results of the hypotheses were formulated by using partly exploratory factor analysis (EFA), partly confirmatory factor analysis (CFA), and structural equation modeling (SEM) techniques. The findings expose that device quality is an independent factor, and an antecedent of user interface design quality and system quality. The research also discloses that user interface design quality is a prerequisite of system quality and information quality. In the research, system quality and information quality are key factors affecting customers’ intention to adopt MB. Further, the results confirm that system quality has a statistically significant effect on information quality. However, the effect of device quality on information quality is insignificant. It is expected that the research gives valuable insights for not only bank managers but also software engineers who are going to develop MB systems.